Precipitation kinetics of dilute Cu-W alloys during low-temperature ion irradiation. (November 2016) - Zhang, Xuan; Beach, John A.; Wang, Miao; Bellon, Pascal; Averback, Robert S.
Abstract: The kinetics of W precipitation in dilute Cu-W alloys during room temperature irradiation is investigated using in situ electrical resistivity measurements and transmission electron microscopy. For a series of alloys with W concentrations varying from ∼1 at.% to 6 at.%, resistivity measurements show that high dose irradiation leads to steady-state solubility values which are concentration dependent, while electron microscopy shows that the precipitate structures are stabilized at high doses at a size of about 2 nm. These steady states are independent of the initial alloy microstructure: whether it is a solid solution or it contains large W precipitates within the Cu matrix. The effective tracer impurity diffusion coefficient of W in Cu in energetic displacement cascades is determined by in situ electrical resistivity measurements on multilayer structures of alternating Cu/W layers, yielding a value of 2.1 nm 2 /dpa. These multilayer structures are observed to undergo significant interfacial roughening during irradiation, showing signs of transforming from a 2-dimensional to 3-dimensional structure under prolonged irradiation. A model based on a dynamical competition between recoil mixing and thermal spike diffusion is proposed to explain these various results; it is implemented in kinetic Monte Carlo simulations. Graphical abstract: